Análisis del juicio coactivo, y sus incidencias en la aplicación de medidas cautelares - Olalla Pilco, Diego Patricio (2016)
Coercive is a procedure undoubtedly agile, fast, and one might even say accelerated, and gives effect to the collection of items, dividends, up, to the institutions of the state and that are generated by the public service values. Analyzing more carefully this aspect, and speaking directly of coercive judgment, it is analyzed in this research work, the various concepts that express the contradictions between the way that the relief and recovery of due values apply. If directly coercive jurisdiction is analyzed, the same as is set out in COOTAD and maintaining the Code of Civil Procedure, we note that there exists for the affected power to defend within the Administrative Procedure person, having to resort to pending exception before a judge of administrative litigation, attentive to the constitutional principle of simplicity. With the main premise studying whether coercive is a judgment or an administrative measure, and in this sense aspects of substance and form that characterize a trial and to an administrative act are discussed. Applying the methodology of scientific type, using tools such as the survey, a feasible outcome will be for a possible reform of the Code of Civil Procedure; And above all things should be kept in mind that the Republic of Ecuador, as established by the Constitution is a State of Rights, which is promoted above all things fairness, good treatment, equal opportunities, and dignity, immediately and effectively to the Ecuadorian society in general justice is provided. In this case the COOTAD no effective the principle of impartiality, which causes the problem in unequal conditions with direct reference to his accuser.